2018
DOI: 10.3892/etm.2018.5814
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs in the serum exosomes of methamphetamine-dependent rats vs. ketamine-dependent rats

Abstract: Drug abuse is a public health and social problem. A number of studies have reported that drug addiction is associated with microRNAs (miRNAs). By comparing the expression of miRNAs in the serum exosomes of methamphetamine-dependent and ketamine-dependent rats, the aim of the present study was to provide insights into the miRNA-mediated associations between the two groups. Published results on conditioned place preference (CPP) in rats conditioned by methamphetamine and ketamine were replicated. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The current study demonstrated the downregulation of NAc miR-219p-5p targeting AT1R after METH SA, compared with yoked-METH and Saline rats. Current findings extend the increasing bodies of research that have demonstrated METHenabled alterations in a number of NAc miRNA expressions associated with various neuronal activities, including metabolism, apoptosis, autophagy, and immune response, potentially via the mitogen-activated protein kinase, CREB, G-protein-coupled receptor, and gonadotropin-releasing hormone signaling pathways (Zhu et al, 2015;Bai et al, 2016;Sim et al, 2017;Li et al, 2018;Zhang et al, 2018). A clinical study has also identified numerous miRNAs as negative regulators in patients with METH use disorder.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The current study demonstrated the downregulation of NAc miR-219p-5p targeting AT1R after METH SA, compared with yoked-METH and Saline rats. Current findings extend the increasing bodies of research that have demonstrated METHenabled alterations in a number of NAc miRNA expressions associated with various neuronal activities, including metabolism, apoptosis, autophagy, and immune response, potentially via the mitogen-activated protein kinase, CREB, G-protein-coupled receptor, and gonadotropin-releasing hormone signaling pathways (Zhu et al, 2015;Bai et al, 2016;Sim et al, 2017;Li et al, 2018;Zhang et al, 2018). A clinical study has also identified numerous miRNAs as negative regulators in patients with METH use disorder.…”
Section: Discussionsupporting
confidence: 74%
“…A clinical study has also identified numerous miRNAs as negative regulators in patients with METH use disorder. The majority of studies have used the model of locomotor sensitization and conditioned place preference induced by METH that involves repeated passive administration of METH (Zhu et al, 2015;Li et al, 2018). Two recent studies have investigated the changes in miRNA in rats selfadministering METH.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of research into METH abuse and vesicular bodies lies in understanding synaptic vesicles, which are crucial for interneuronal communication, but EVs also contribute to the intercellular communication of the whole nervous system [102]. One paper sequenced the miRNAs found in serum-derived EVs of METH-dependent rats, identifying a total of 301 differentially expressed miRNAs [103]. Four of the differentially regulated miRNA were miR-218b, miR-194-5p, miR-152-3p, and miR-22-3p, which were also noted to be differentially regulated in ketamine dependence [103].…”
Section: Methamphetaminementioning
confidence: 99%
“…One paper sequenced the miRNAs found in serum-derived EVs of METH-dependent rats, identifying a total of 301 differentially expressed miRNAs [103]. Four of the differentially regulated miRNA were miR-218b, miR-194-5p, miR-152-3p, and miR-22-3p, which were also noted to be differentially regulated in ketamine dependence [103]. Elevated serum levels of miR-194-5p have been associated with cancers of peripheral organs such as the kidneys and liver [104,105].…”
Section: Methamphetaminementioning
confidence: 99%
“…As a result, depending on whether the producer cells are healthy or pathologic, EVs will carry markers corresponding to the state of the cells [ 40 , 43 ]. With respect to drug use, EVs have been used to establish signatures linked to methamphetamine, heroin, and alcohol abuse [ 57 , 58 , 59 ]. EVs released by substance-using HIV-infected individuals are known to exhibit pathogenic properties, including increases in cell adhesion, actin reorganization, secretion of metalloproteases, and chemotactic migration toward the HIV secretome [ 42 ].…”
Section: Introductionmentioning
confidence: 99%